3D spacer fabric based multifunctional triboelectric nanogenerator with great feasibility for mechanized large-scale production. (September 2016) - Zhu, Minshen; Huang, Yang; Ng, Wing Sum; Liu, Junyi; Wang, Zifeng; Wang, Zhengyue; Hu, Hong; Zhi, Chunyi
Abstract: Harvesting energy from environment (e.g. human motions), is a cost-effective strategy to power the personal electronics. Triboelectric nanogenerators (TENGs) have been proven to be an effective device that can scavenge the biomechanical energy from human motions. However, the compatibility for wearing and mechanized production, two critical criterions for practical applications, of the TENGs remain as challenges. Here, we demonstrated an elegantly designed 3D knitted spacer fabric based TENG by utilizing the vertical contact electrification between two polymers with different tribo-polarities. The open circuit voltage of the one single TENG pixel of as-fabricated TENG reaches more than 3 V, while the short circuit current reaches around 0.3 μA. The output power reaches 16 μW, whereas it can be delicately tuned by controlling the number of TENG pixels involved. As a power source, the as-fabricated TENG can continuously lit up the LEDs. In addition, the as-fabricated TENG shows outstanding ability to effectively monitor the human motions. Furthermore, the ability of in situ sensing the pressure of a foot during the human walking was successfully realized. Our study reports a novel large-scale-fabrication method of TENGs compatible with mechanized production, which shows outstanding output performance as well as the excellent smart sensing abilities. Graphical abstract: Highlights: Multifunctional TENGs based on 3D spacer fabric feasible to mechanized production. Excellent ability in monitoring and identifying human motions. In situ sensing the pressure on foot showing great potential in health caring.